Impact of political connections on Chinese export firms' performance – Lessons for other emerging markets - Sharma, Piyush; Cheng, L.T.W.; Leung, T.Y. (2020)
© 2019 Elsevier Inc. This paper explores the differences in the impact of political connections on the performance of Chinese exporter and non-exporter firms and among three types of exporter firms; private-owned (POE), local state-owned (LSOE) and central state-owned (CSOE). Our sample has 7326 firm-year observations from 1945 firms listed on Shanghai and Shenzhen stock exchanges during 2006–2010 period. Using export sales, ratio of export to total sales and return on assets as the performance indicators, we find significant positive effects of political connections on Chinese firms' decisions to enter export markets and on their subsequent export performance. We also find significant differences in these effects based on the type of firm ownership (i.e., POE, LSOE and CSOE). Besides extending research linking political connections and export performance, our study would also help researchers, managers and policy-makers in the emerging markets understand the pros and cons of using political connections to drive export performance.